The Effect Of Financial Health Levels To The Indication Of Financial Statement Fraud In Transportation Sector - Sharon Callista Hanjaya; Sylvia Fettry (Kesatuan Press, 2021)
Because of app-based transportation, traditional transportation companies are being abandoned because in terms of practicality, they are less accessible to various groups of people. Therefore, traditional transportation companies compete difficultly and have financial pressure. One example of financial pressure is poor financial health. Based on the Fraud Triangle theory, it is said that if a company is under pressure, the possibility of committing fraud will increase. This study is conducted to find empirical evidence whether the level of financial health could affect the possibility of financial statement fraud. This study is expected to provide knowledge to investors and potential investors how to use the Altman's Z-Score analysis method as a measuring tool for financial health level and the Beneish M-Score as a financial statement fraud red flag measurement tool, in order to avoid fraud in the future. The research method used is the method of causality. The data collected is secondary quantitative data in the form of financial statements of companies in the land public transportation industry for the period of year 2015 until 2019. Descriptive and verificative analysis will be done on these data. After conducting the analysis, it can be concluded that the level of financial health has a significant effect on financial statement fraud indications. But there are many other factors that can explain changes in the likelihood of a company committing financial statement fraud such as opportunity, rationalization and various other types of pressure.